Educational TechnologyBridging the Gap Between Youth and Adult Learners of the 21st Century - Joshua Lane Miller (Adult Education Research Conference, 2015)
21st Century learners require activities that move beyond the traditional teacher-centered transmission model of education. This speculative essay considers education through an emphasis on collaboration, cooperation, and communication. This focus holds the capacity to bridge K-12 learning theories with those of Adult Education through the effective integration of educational technology.
Keywords: educational technology; adult education